Inflation in Poland : How Much Can Globalization Explain? - Allard, Celine (IMF Working Papers; Working Paper ;, 2007)
This paper analyses how globalization has affected inflation in the New EU Members States (NMS), and Poland in particular, since 1995. It finds prices have become less sensitive to domestic economic conditions as trade integration rose, possibly because monetary policy incentives increasingly shifted toward meeting price stability objectives. Quantitatively, globalization appears to have lowered Polish prices by 1\2 to 1 percentage point annually since 1995, substantially more than in advanced economies. However, future inflation-dampening effects in the NMS are likely to be smaller as the pace of increases in trade openness moderates.